GENERALIZATION AND CHARTOMETRIC ANALYSIS OF THE SITNICA RIVER NETWORK SYSTEM - Jandžiković, Bojana (Bulletin of Natural Sciences Research, 2019)
The basin of Sitnica river represents a good option for chartometric investigation. In modern hydrology, digital and GIS analyses play very important role today. In this research we were able to obtain the main properties of the river basin and river network with the help of digital line generalization. The results from the two kind of maps with two scales 1:25.000 and 1:50.000 showed differences in length of the main river Sitnica and its tributaries. These differences may be included into the analysis of the Sitnica river network. For the first time it was concluded that the Sitnica river has bi-polar dendritic parallel network. The 80% of right tributaries have angles between 2° and 5° degrees in direction of the Sitnica river. The left tributaries have angles between 1° and 2° degrees with the main water-course.